2020
DOI: 10.26714/lensa.8.1.2018.1-21
|View full text |Cite
|
Sign up to set email alerts
|

The Shift in Gender Roles in Amy Tan’s 'The Joy Luck Club' and Khaled Hosseini’s 'The Kite Runner'

Abstract: The unfair gender roles under patriarchal system are constructed to preserve gender inequality between men and women. Gender role practices extend gradually to maintain the male hegemony to make women powerless because female traditional gender roles (femininities) create dependency to men. Men are assigned to masculinities equipped with power, whereas women are ascribed to femininities to set boundaries that limit their movement. Yet, the increase of female awareness of gender equality has changed this situat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…However, one similarity exists across the globe: gender roles are not static and can change as the needs of society change. The increase in women’s education, employment and participation in the economy are some of the factors that contribute to shifts in gender roles [14]. While shifts in gender roles are more pronounced in European countries [15], changes in African countries are also being observed.…”
Section: Introductionmentioning
confidence: 99%
“…However, one similarity exists across the globe: gender roles are not static and can change as the needs of society change. The increase in women’s education, employment and participation in the economy are some of the factors that contribute to shifts in gender roles [14]. While shifts in gender roles are more pronounced in European countries [15], changes in African countries are also being observed.…”
Section: Introductionmentioning
confidence: 99%
“…This is possible because literature reflects author's experience and inspiration from the world. For example, in The Joy Luck Club and The Kite Runner novel, men's role is dominant in public settings (Afandi, 2020). It was only when woman characters were getting opportunities in education and occupation, their role started to change.…”
Section: Introductionmentioning
confidence: 99%
“…They found two kinds gender roles exist in the novel's society; traditional and progressive. Second, a study analyzed gender roles shifting in The Joy Luck Club and The Kite Runner novel using Marx's conflict theory (Afandi, 2020). The study found the shift roles increased alongside the increasing female education and job opportunity.…”
Section: Introductionmentioning
confidence: 99%